Stabilized Co‐Free Li‐Rich Oxide Cathode Particles with An Artificial Surface Prereconstruction. Issue 35 (6th August 2020) - Zhu, Zhi; Gao, Rui; Waluyo, Iradwikanari; Dong, Yanhao; Hunt, Adrian; Lee, Jinhyuk; Li, Ju
Abstract: Li‐rich metal oxide (LXMO) cathodes have attracted intense interest for rechargeable batteries because of their high capacity above 250 mAh g −1 . However, the side effects of hybrid anion and cation redox (HACR) reactions, such as oxygen release and phase collapse that result from global oxygen migration (GOM), have prohibited the commercialization of LXMO. GOM not only destabilizes the oxygen sublattice in cycling, aggravating the well‐known voltage fading, but also intensifies electrolyte decomposition and Mn dissolution, causing severe full‐cell performance degradation. Herein, an artificial surface prereconstruction (ASR) for Li1.2 Mn0.6 Ni0.2 O2 particles with a molten‐molybdate leaching is conducted, which creates a crystal‐dense anion‐redox‐free LiMn1.5 Ni0.5 O4 shell that completely encloses the LXMO lattice (ASR‐LXMO). Differential electrochemical mass spectroscopy and soft X‐ray absorption spectroscopy analyses demonstrate that GOM is shut down in cycling, which not only stabilizes HACR in ASR‐LXMO, but also mitigates the electrolyte decomposition and Mn dissolution. ASR‐LXMO displays greatly stabilized cycling performance as it retains 237.4 mAh g −1 with an average discharge voltage of 3.30 V after 200 cycles. More crucially, while the pristine LXMO cycling cannot survive 90 cycles in a pouch full‐cell matched with a commercial graphite anode and lean (2 g A −1 h −1 ) electrolyte, ASR‐LXMO shows high capacity retention of 76% after 125 cycles in full‐cell cycling. Abstract : Global oxygen migration induced natural surface reconstruction destabilizes layered Li‐rich phases and intensifies electrolyte decomposition during cycling, aggravating voltage fading and full‐cell degradation. An artificial surface prereconstruction is conducted for Co‐free Li‐rich particles with a molten‐molybdate leaching, which creates a crystal‐dense high‐voltage‐spinel shell to prevent oxygen loss, mitigate voltage fading, and stabilize the full‐cell cycling.